2022
DOI: 10.7150/jca.56777
|View full text |Cite
|
Sign up to set email alerts
|

The correlation and role analysis of SLC30A1 and SLC30A10 in cervical carcinoma

Abstract: Background: SLC30 family genes, also known as ZnT family genes, can keep cellular zinc levels within a physiological range by exporting zinc to extracellular space or by isolating zinc in the specific regions of cytoplasm when cellular zinc concentrations are elevated in human cells. There are growing evidences that dysregulated expression of SLC30 family genes can potentially influence tumorigenesis. However, the expression and prognostic value of SLC30 family genes in cervical carcinoma are poorly characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These results suggest the involvement of the zinc-binding, metal-regulatory transcription factor MTF-1, which is activated by the release of zinc from metallothionein (MT) upon metal overload or oxidative stress [31]. Interestingly, the up-regulation of SLC30A1, which encodes a proton-coupled zinc antiporter involved in the efflux of zinc from cells to prevent toxicity, was also observed with increasing exposure duration [32].…”
Section: Discussionmentioning
confidence: 92%
“…These results suggest the involvement of the zinc-binding, metal-regulatory transcription factor MTF-1, which is activated by the release of zinc from metallothionein (MT) upon metal overload or oxidative stress [31]. Interestingly, the up-regulation of SLC30A1, which encodes a proton-coupled zinc antiporter involved in the efflux of zinc from cells to prevent toxicity, was also observed with increasing exposure duration [32].…”
Section: Discussionmentioning
confidence: 92%
“…From these elucidations, computationally designed derivatives could be obtained by optimizing the biological activity. In 2022, Zhang et al (2022) identified that neopeltolide could inhibit the high expression of the SLC30A10 gene, which belongs to the ZnT gene family that is strongly related to tumor development and metastasis.…”
Section: Potential Anticancer Studiesmentioning
confidence: 99%
“…From these elucidations, computationally designed derivatives could be obtained by optimizing the biological activity. In 2022, Zhang et al (2022) identified that neopeltolide could inhibit the high expression of the SLC30A10 gene, which belongs to the ZnT gene family that is strongly related to tumor development and metastasis. Despite all the in vitro studies that have demonstrated the high cytotoxic effects of neopeltolide and its derivatives against various cancer cell lines, there is still no in vivo evidence that allows taking the next step towards a clinical evaluation.…”
Section: Complex Bc1mentioning
confidence: 99%